Web portal: total challenge - Martins, Tiago (2012)
The Web is an extraordinary success, for its simplicity. This simplicity has brought disadvantages, because with vast amounts of information available, the search is a difficult, time-consuming and sometimes inefficient task, creating the need for a strategic information management. To overcome this need came the portals. The characteristics of portals differ from each other, which made them appear different definitions. Also arose several classifications of portals, one of which considers three dimensions to classify them: the scope of content, the aim of the portal and the range of its intended users. With this work, the authors intend to build a Web Portal to support one or more serious games. A database is shared with the Web Portal. This portal will serve to make an interface between the user and the games, for the dissemination and support of these and as a platform for managing and monitoring results.